PTH-130 Attitudes of Medical Students Towards Gastroenterology Teaching in The UK: A BSG Survey. (17th August 2016) - Cheung, VTF; Johnson, GJ
Abstract : Introduction: Little is known about how undergraduate gastroenterology teaching is delivered in the UK. Our project aims to inform how the BSG could assist in this and to build links with students with an interest in gastroenterology. Methods: A survey containing 27 questions related to undergraduate gastroenterology training was compiled on surveymonkey.com. We emailed the UK medical school deans and local gastroenterology champions asking them to send out the survey to their medical students. In 10 weeks, 110 students from 12 medical schools responded. Results: 83% felt that there was adequate exposure to gastroenterology. 75% felt that their training made them confident in managing gastroenterology patients. 9% had a student gastroenterology society (41% don't have one, 50% not sure). They usually interact via email or Facebook. 59% would consider a career in gastroenterology (53% interested in subject, 24% inspirational consultants, 24% clinic experience, 10% endoscopy experience). 41% would not consider a career in gastroenterology (49% mind set on another specialty, 14% too much endoscopy, 14% out of hours requirement, 7% don't want to be medical registrar, 6% don't want to do CMT training, 3% complexity of patients, 3% low financial reward compared to other specialties). Year group sizes ranged from 40–400. 71% had an integrated curriculum whilst 29% had traditional. 20-100% would have a gastroenterology block in their training. Gastroenterology blocks lasted from 1–12 weeks usually in 3 rd year. Teaching consisted of lectures (99%), small group work (65%), PBL (63%), bedside teaching (65%) and others (13%> GP, home visit, prosection). 65% had gastroenterology and surgical training integrated. 72% said there was a copy of the Gastroenterology syllabus/set of learning objectives within the MBBS curriculum and 60% had read them. Medical final exams involved SBA (83%), short answers (36%), MCQs (65%) and OSCEs (26%). Suggestions for improving gastroenterology training: More consultant training Expert patients as a learning tool Online teaching tools Simulation days Mandatory gastroenterology block More hepatology Conclusion: There appears to be adequate exposure to gastroenterology training in UK medical schools. Training seems to enable medical students to feel comfortable managing gastroenterology patients in their foundation years. However, there remains scope for enhancing gastroenterology training with students wanting longer dedicated attachments to gastroenterology firms and BSG to do taster days/revision courses/simulation days. Student gastroenterology societies are rare and BSG can help in promoting these. 60% students would consider a career in gastroenterology with interest in the subject being the overriding reason. BSG should capitalise on this and establish links with medical students early in their training. Disclosure of Interest: None Declared